Investment, credit constraints and public policy in a neoclassical adjustment cost framework; Investitionen, Kreditrationierung und Agrarpolitik in einem dynamischen neoklassischen Modell mit Anpassungskosten - Lukas Čechura (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2008)
This paper deals with the analysis of the impact of credit rationing on the farmer's economic equilibrium and the analysis of different policy scenarios in a derived neoclassical adjustment cost framework. The theoretical model is an optimal dynamic investment model, in which the upper bound on investment is introduced. The limit of the investment enables to analyse the consequence of the occurrence of credit rationing on farmer's capital accumulation, investment and supply. The method of optimal control is used to solve the optimization problem. The results show that the occurrence of credit rationing may significantly determine a farmer's economic equilibrium. Then the analysis of defined policy scenarios suggests that a loan guarantee efficiently solves the problem of the occurrence of external credit rationing. Interest rate subsidy may produce overinvestment and, thus, increases the probability of occurrence of the crowdingout effect, especially in the group of non-credit constraint farmers. Moreover, as far as the cost of agricultural policy is concerned, other agricultural support tools are less effective. The numerical application shows that the farmer's economic equilibrium is mostly sensitive to the initial bound on investment, the parameter of the cost function, the price, the level of technology and the discount rate. Finally, if the uncertainty is introduced, then the level of investment spending and capital accumulation is lower. – – Das Diskussionspapier beschäftigt sich den Einflüssen der Kreditrationierung auf das unternehmerische Verhalten von landwirtschaftlichen Betriebsleitern und wie dieses durch agrarpolitische Eingriffe beeinflusst wird. Die Effekte werden mit Hilfe eines dynamischen neoklassischen Investitionsmodels mit unteren und oberen Schranken analysiert. Neben der Investitionstätigkeit werden in diesem Kontext die Konsequenzen der Kreditrationierung auf die betriebliche Kapitalakkumulation und das landwirtschaftliche Angebot untersucht. Die Modelle werden mit Hilfe der Kontrolltheorie gelöst. Die Ergebnisse zeigen, dass die Kreditrationierung die Entwicklungsmöglichkeiten der landwirtschaftlichen Betriebe erheblich einschränken. Darüber hinaus ergab sich bei der Analyse von Politikszenarien, dass sich die negativen Effekte der Rationierung durch die Einführung von Bürgschaften effizient reduzieren lassen. Zinssubventionen können dagegen zu einer Überinvestition und Mitnahmeeffekten in der Gruppe der Landwirte führen, die nicht kreditrationiert sind, wodurch auch eine Verdrängung privater zugunsten öffentlich geförderter Investitionen erfolgt. Andere agrarpolitische Eingriffe sind weniger effektiv, insbesondere wenn die Kosten der Durchführung dieser Maßnahmen berücksichtigt werden. Simulationsberechnungen zeigten, dass das langfristige Gleichgewicht der Betriebe durch den anfänglichen Zugang zu Krediten, der Parametern der Kostenfunktion, den Produktpreis, dem Stand der Technologie und dem Zinssatz beeinflusst wird. Wird Unsicherheit in dem Model berücksichtigt, so führt dies generell zu einer geringeren Investitionstätigkeit und zu einer geringeren Kapitalakkumulation.
urn:nbn:de:gbv:3:2-11443
Keywords: C61; Q12; Q14; Q18; 330; Kreditrationierung; Investitionen; Kapital; EAGFL (Europäische Ausrichtungs-und Garantiefond für die Landwirtschaft); Dynamische Anpassungskosten und langfristiges Gleichgewicht. Credit constraint; investment; capital; SGAFF (Supporting and Guarantee Agricultural and Forestry Fund); Adjustment cost and farmer's economic equilibrium.